FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH KABUPATEN ENDE DENGAN PEMANFAATAN TEKNOLOGI INFORMASI SEBAGAI VARIABEL MODERASI - Reu, Fransiskus Marlon (Jurusan Akuntansi Politeknik Negeri Pontianak, 2024)
This study aims to test and analyze the influence of human resource competence, Government Internal Control System on the Quality of Regional Financial Reports with the Utilization of Information Technology as a moderating variable. This study uses a quantitative descriptive method with primary data in the form of questionnaires given to 106 respondents. Data analysis was carried out using validity and reliability tests, classical assumption tests, multiple linear regression, hypothesis testing through t-tests and F-tests, and determination coefficient tests. The results of the study indicate that human resource competence has no significant effect on the quality of financial reports in Ende district. The Government Internal Control System variable also gives results that have a negative effect on the quality of financial reports. the results of testing using the moderation variable of information technology utilization obtained the result that the Utilization of information technology cannot moderate the influence of human resource competence on the quality of regional financial reports, while the utilization of information technology can moderate the influence of the government internal control system in Ende district. The independent variables in this study have a simultaneous influence on the quality of financial reports of 85.5% while the other 14.5% is influenced by other variables not explained in this study.